2009
DOI: 10.1097/hp.0b013e3181a9ab15
|View full text |Cite
|
Sign up to set email alerts
|

Radon Exhalation Rates From Building Materials Using Electret Ion Chamber Radon Monitors in Accumulators

Abstract: An electret ion chamber (EIC) radon monitor in a sealed accumulator measures the integrated average radon concentration at the end of the accumulation duration. Theoretical equations have been derived to relate such radon concentrations (Bq m(-3) ) to the radon emanation rate (Bq d(-1)) from building materials enclosed in the accumulator. As an illustration, a 4-L sealable glass jar has been used as an accumulator to calculate the radon emanation rate from different granite samples. The radon emanation rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The closed chamber method (CCM) proposed by Chao et al is essentially one kind of accumulation method which can take into account the leakage of the accumulation chamber and the back diffusion rate, so it is widely used in the measurement of the radon exhalation rate of building materials [6]. Due to a possible misunderstanding of the radon exhalation model, the CCM sometimes might be misused during measurements, especially in pre-treatments of building materials [7][8][9]. Chao discussed the difference between the onedimensional model and the three-dimensional model by comparing experiments (sealing on four sides versus no sealing on surfaces), but no more theoretical analysis was given and no details on how to make different models consistent were shown [10].…”
Section: Introductionmentioning
confidence: 99%
“…The closed chamber method (CCM) proposed by Chao et al is essentially one kind of accumulation method which can take into account the leakage of the accumulation chamber and the back diffusion rate, so it is widely used in the measurement of the radon exhalation rate of building materials [6]. Due to a possible misunderstanding of the radon exhalation model, the CCM sometimes might be misused during measurements, especially in pre-treatments of building materials [7][8][9]. Chao discussed the difference between the onedimensional model and the three-dimensional model by comparing experiments (sealing on four sides versus no sealing on surfaces), but no more theoretical analysis was given and no details on how to make different models consistent were shown [10].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the magnitude of the flux measurements that we have previously measured and that are used in our Monte Carlo analysis, on average, the fluxes used in this study are higher than what had been previously reported in the published literature. Flux values from granite in the published literature were reported for over 500 stones, in several different countries, and measured radon fluxes ranged from 0.01 to 129 Bq m −2 h −1 (0.03-323.9 pCi ft −2 h −1 ) [2,[9][10][11][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. In our primary model, our maximum flux was 78.93 Bq m −2 h −1 (198.2 pCi ft −2 h −1 ), which is higher than the flux values reported in all but two studies [29,40].…”
Section: Discussionmentioning
confidence: 99%
“…The air volume of the jar has some radon concentration at the time of the sealing which will effects our measurement results. An empty jar is used to determine the ambient (background) radon concentration as advised by Kotrappa and Stieff [4]. All measurements were performed simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…Radon exhalation can be defined as the escape of radon gas from porous materials into the atmosphere [1]. The radon gas released from the unit surface area per unit time is called as radon area (surface) exhalation rate [4].…”
Section: A Preliminary Study To Determine the Radon Exhalation Rates ...mentioning
confidence: 99%
See 1 more Smart Citation